Meta Analisis Pengaruh Problem Based Learning dan Virtual Laboratory Terhadap Hasil Belajar Siswa - Deno Puyada; Rusnardi Rahmat Putra (invotek, 2018)
Abstract: A meta-analysis was conducted to synthesize existing studies comparing the effects of Problem Based Learning and virtual laboratory versus traditional instructional media on student learning outcomes. Sixty-three studies were placed in this meta-analysis, and the results showed that Problem Based Learning and virtual laboratory learning media were more effective than instructional methods. The results of this study indicate that Problem Based Learning and virtual laboratory learning media clearly have a more positive effect on student learning than instructional methods. Keywords : Virtual Laboratory, Students Achievement, Problem Based Learning